2002
DOI: 10.1161/hc0302.102598
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vein Graft Disease Using High-Resolution Magnetic Resonance Angiography

Abstract: Background-The application of previous magnetic resonance (MR) angiography techniques has enabled noninvasive differentiation between patent and occluded coronary artery bypass grafts. However, the detection of graft stenosis remains difficult. The purpose of our study was to determine the accuracy of high-resolution navigator-gated 3-dimensional (3-D) MR angiography in detecting vein graft disease. Methods and Results-MR angiography was performed in addition to coronary angiography with quantitative coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…Promising results have been recently reported for magnetic resonance imaging (MRI). Langerak et al [14] Fig. 3 Seventy-one-year-old man with a recent non-Q wave myocardial infarction who underwent CABG surgery with LIMA to LAD and right internal mammary artery (RIMA) to obtuse marginal branch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising results have been recently reported for magnetic resonance imaging (MRI). Langerak et al [14] Fig. 3 Seventy-one-year-old man with a recent non-Q wave myocardial infarction who underwent CABG surgery with LIMA to LAD and right internal mammary artery (RIMA) to obtuse marginal branch.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary angiography (CA) is still the diagnostic tool of reference for evaluating the status of grafts and coronary arteries; however, it is an invasive procedure, requires hospitalization and is characterized by a small but relevant risk of untoward events [5]. Attempts have been made to assess venous graft patency with non-invasive methods, including electron beam computed tomography (EBCT) [6][7][8] and magnetic resonance imaging (MRI) [9][10][11][12][13][14][15], with encouraging results. However, a routine use of these two modalities can be limited by inadequate scan coverage, clinical availability and higher costs for EBCT or long acquisition time, lower spatial resolution and claustrophobia for MRI.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has been renewed interest to assess the presence of graft stenoses. A recent single-center study showed an intermediate sensitivity but high specificity for detection of focal graft stenoses [22] (Figure 11). …”
Section: Imaging Of the Patency Of Bypass Graftsmentioning
confidence: 97%
“…However, imaging is hindered by the presence of sternal wires, graft markers or surgical clips that create local field inhomogeneities and susceptibility artifacts ( Figure 10). The patency of bypass grafts can be ascertained if evidence of blood flow can be identified in at least two levels along the course of the graft [22][23][24][25]. Even using slow conventional CMRA techniques, the patency of bypass grafts can be accurately assessed.…”
Section: Imaging Of the Patency Of Bypass Graftsmentioning
confidence: 99%
“…Obwohl die Schichtdicke beim MRT durch längere Aufnahmezeiten von 6 mm auf 3 mm verringert werden kann, lässt sich dies nicht an einer verbesserten Bildqualität erkennen [41]. Mit der Navigatortechnik fand sich an 38 Patienten eine Sensitivität von 65% bis 82% bei einer Spezifität von 82% bis 88% für die Erkennung von ≥ 50%igen Stenosen in Bypassgefäßen [30].…”
Section: Gibt Es Alternativen?unclassified